Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set: 18

Answer

$(f-g)(x)= -x^2-2x+8$

Work Step by Step

RECALL: $(f-g)(x) = f(x) - g(x)$ Using the formula above gives: $(f-g)(x) = (-2x+3)-(x^2-5) \\(f-g)(x)= -2x+3-x^2-(-5) \\(f-g)(x)= -2x+3-x^2+5 \\(f-g)(x)= -x^2-2x+8$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.